2021
DOI: 10.3390/ijms221910790
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Mitochondrial Metabolism Leads to Selective Eradication of Cells Adapted to Acidic Microenvironment

Abstract: Metabolic transformation of cancer cells leads to the accumulation of lactate and significant acidification in the tumor microenvironment. Both lactate and acidosis have a well-documented impact on cancer progression and negative patient prognosis. Here, we report that cancer cells adapted to acidosis are significantly more sensitive to oxidative damage induced by hydrogen peroxide, high-dose ascorbate, and photodynamic therapy. Higher lactate concentrations abrogate the sensitization. Mechanistically, acidosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
3
1
Order By: Relevance
“…Our results suggest that the impact of lactate on the cytosolic catabolism of glucose in cancer cells relies on alternative regulation processes such as the alteration of proton exchanges at the plasma membrane 7 , signalling 50 or epigenetic modulations 51 , that are not exclusive to the cytosol and occurs on longer timescales. Contrastingly, our findings suggest that the metabolic alteration induced by acidosis in cancer 52 56 involves a direct interaction of protons with the cytosolic machinery of glucose catabolism, and can be observed almost instantly in isolated cytoplasmic fractions.…”
Section: Discussioncontrasting
confidence: 87%
“…Our results suggest that the impact of lactate on the cytosolic catabolism of glucose in cancer cells relies on alternative regulation processes such as the alteration of proton exchanges at the plasma membrane 7 , signalling 50 or epigenetic modulations 51 , that are not exclusive to the cytosol and occurs on longer timescales. Contrastingly, our findings suggest that the metabolic alteration induced by acidosis in cancer 52 56 involves a direct interaction of protons with the cytosolic machinery of glucose catabolism, and can be observed almost instantly in isolated cytoplasmic fractions.…”
Section: Discussioncontrasting
confidence: 87%
“…The synergy between acidosis and the PDT efficacy of 1NPs was clearly noticed, similarly to the effects of other complexes. 24 Also, significant inhibition of 1NP phototoxicity was observed under hypoxia (Fig. S6B, ESI†), highlighting the critical role of oxygen in the efficiency of PDT.…”
Section: Resultsmentioning
confidence: 90%
“…3 F–G). Since nicotinamide adenine dinucleotide phosphate (NADPH) could function as a reducing agent and play a significant role in ROS stress response [ [38] , [39] , [40] ], we measured NADPH in lymphoma cells (JeKo-1) and normal stromal NKtert cells treated with or without AF. The results showed that AF caused a moderate increase of NADPH at 2 h in both cell lines, but this increase returned to the basal level at 6 h ( Fig.…”
Section: Resultsmentioning
confidence: 99%